2015
DOI: 10.7314/apjcp.2015.16.7.2915
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of Seven Randomized Control Trials to Assess the Efficacy and Toxicity of Combining EGFR-TKI with Chemotherapy for Patients with Advanced NSCLC who Failed First-Line Treatment

Abstract: Background: Some recent clinical trials have been conducted to evaluate a combination of EGFR-TKI with chemotherapy for advanced NSCLC patients as second-line therapy, but the results on the efficacy of such trials are inconsistent. The aim of this meta-analysis was to evaluate the efficacy and safety of combination of EGFR-TKI and chemotherapy for patients with advanced NSCLC who failed first-line treatment. Materials and Methods: We searched relative trials from PubMed, EMBASE, ASCO Abstracts, ESMO Abstracts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Subgroup meta-analysis stratified for each involved pathway was carried out. Among these, 1 subgroup meta-analysis investigating the EGFR inhibitor revealed a significant benefit in PFS with 4 articles involved and ORR with 6 articles involved than PG group which was consistent with previous studies [ 56 58 ] in first-line or second-line settings. As for toxicity profile, there were more incidence of grade 3 or 4 rash, anemia, diarrhea, and anorexia in combining EGFR targeted therapy group compared to PG group.…”
Section: Discussionsupporting
confidence: 88%
“…Subgroup meta-analysis stratified for each involved pathway was carried out. Among these, 1 subgroup meta-analysis investigating the EGFR inhibitor revealed a significant benefit in PFS with 4 articles involved and ORR with 6 articles involved than PG group which was consistent with previous studies [ 56 58 ] in first-line or second-line settings. As for toxicity profile, there were more incidence of grade 3 or 4 rash, anemia, diarrhea, and anorexia in combining EGFR targeted therapy group compared to PG group.…”
Section: Discussionsupporting
confidence: 88%
“…The data of ORR was 18% and median PFS was 4.2 months for patients with chemotherapy alone in the previous study, but the hematologic and neurologic adverse effects were much more common in chemotherapy group (22). Considering the efficacy and toxicity, afatinib could be an optional choice compared with chemotherapy alone with much (23)(24)(25). Meanwhile, for advanced EGFRpositive patients with acquired resistance, changing to other 1st generation TKIs seemed to be the inefficient treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, a growing number of protocols combining chemotherapy and TKi are currently being tested in both TKF-induced hematological and solid tumors [ 107 , 132 ] [ 133 ], and several trials are evaluating the efficacy of new TKi either alone or in combination with more conventional therapies (NCT02269085; NCT02427620; NCT02315768; NCT01606878; NCT02134912; NCT02511184). Preclinical studies have also demonstrated a substantial advantage of combining classical chemotherapy with TKi: Das and colleagues showed a synergistic effect of Crizotinib and Temozolomide in FIG-ROS1-positive glioblastoma patient-derived cells, paving a route to improve clinical outcome [ 134 ].…”
Section: Future Perspectivesmentioning
confidence: 99%